PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONALDAN TRANSAKSIONAL TERHADAP KINERJA ORGANISASIMELALUI PRAKTIK TQM PADA PT. PELAYARAN NASIONALINDONESIA CABANG SURABAYA - ISBAH D., FALIQUL (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this study was to analyze the effect of transformational and transactional leadership styles on organizational performance through the practice of total quality management at PT. Pelayaran Nasional Indonesia in Surabaya. With a population of 64 employees, this study used quantitative research, where the sample is employees at PT. Pelayaran Nasional Indonesia Cabang Surabaya that around 54 employees were determined using Proportionate Stratified Random Sampling. Statistical analysis method used is the approach of structural equation modeling (SEM) software by using partial least square (PLS) 2.0 M3. The results of the study describes the style of transformational and transactional leadership significantly influence the performance of the organization, and style of transformational and transactional leadership significantly influence the practice of total quality management, and the practice of total quality management significantly influence the performance of the organization, as well as the style of transformational and transactional leadership significantly influence organizational performance mediated total quality management practices. Keywords: Transformational leadership, transactional, TQM and organizational performance<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />